1994
DOI: 10.1002/zaac.19946200810
|View full text |Cite
|
Sign up to set email alerts
|

Metallderivate von Molekülverbindungen. VIII. catena‐Poly[(2,5,8‐trioxanonan‐O2,O5) lithium‐methylphosphanid] — eine Verbindung mit meso‐Helix‐Struktur

Abstract: Professor Wilhelm Preetz zum 60. Geburtstage gewidmetInhaltsiibersicht. Nach Untersuchungen von Fritz u. a. [lo] wird in 1,2-Dimethoxyethan oder Bis(2-methoxyethy1)etherl) gelostes Methylphosphan bei -60°C durch Lithium-n-butanid in n-Hexan metalliert. Beim Abkuhlen der von Kohlenwasserstoffen weitgehend befreiten Ansatze auf wiederum -60°C kristallisiert (1,2-Dimethoxyethan-O,O')lithiurn-(1) bzw. (2,5,8-Trioxanonan-@,OS)1ithium-methylphosphanid (2) in farblosen Quadern aus. Nach einer Rontgenstrukturanalyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Structures: Previous structure investigations have shown that monolithium phosphanides MPHR 1 and MPR 2 2 display -M-P-M-P-chains of linked MP groups [6,7] (e. g. polymeric LiPH 2´D ME, LiPHMe´DME, LiPPh 2´2 THF; DME MeOCH 2 CH 2 OMe; for more complex structures of lithium and sodium phosphanides see ref. [8]).…”
mentioning
confidence: 99%
“…Structures: Previous structure investigations have shown that monolithium phosphanides MPHR 1 and MPR 2 2 display -M-P-M-P-chains of linked MP groups [6,7] (e. g. polymeric LiPH 2´D ME, LiPHMe´DME, LiPPh 2´2 THF; DME MeOCH 2 CH 2 OMe; for more complex structures of lithium and sodium phosphanides see ref. [8]).…”
mentioning
confidence: 99%
“…They have successfully isolated two different polygons of higher numbers of sides constructed by simple, bent exobidentate organic ligands and two-coordinate Cu I ions in the presence of different molecular templates [85]. Similar to helix, several 1D meso-helix coordination polymers have been characterized [86][87][88]. As shown in Fig.…”
Section: Supramolecular Isomers Related To the Helicesmentioning
confidence: 96%
“…The latter formed a polymeric meso helix. 65 The preparations of LiH(Bu'P),, Li,(Bu'P),, and K,(Pr'P), together with spectroscopic data have appeared.66 The structures and reactivity of three new lithium (fluorosilyl)phosphanides, (7), (8), and ( 9 2,6-mes,},(Et20),]. There were Li-Ph interactions at one lithium, the other being solvated with Et20.86…”
Section: Utmentioning
confidence: 99%